Cell-Specific Promoters Enable Lipid-Based Nanoparticles to Deliver Genes to Specific Cells of the Retina In Vivo - Wang, Yuhong (Theranostics, 2016)
Non-viral vectors, such as lipid-based nanoparticles (liposome-protamine-DNA complex [LPD]), could be used to deliver a functional gene to the retina to correct visual function and treat blindness. However, one of the limitations of LPD is the lack of cell specificity, as the retina is composed of seven types of cells. If the same gene is expressed in multiple cell types or is absent from one desired cell type, LPD-mediated gene delivery to every cell may have off-target effects. To circumvent this problem, we have tested LPD-mediated gene delivery using various generalized, modified, and retinal cell-specific promoters. We achieved retinal pigment epithelium cell specificity with vitelliform macular dystrophy (VMD2), rod cell specificity with mouse rhodopsin, cone cell specificity with red/green opsin, and ganglion cell specificity with thymocyte antigen promoters. Here we show for the first time that cell-specific promoters enable lipid-based nanoparticles to deliver genes to specific cells of the retina in vivo. This work will inspire investigators in the field of lipid nanotechnology to couple cell-specific promoters to drive expression in a cell- and tissue-specific manner.